Amphoteric Membranes Based on Sulfonated Polyether Ether Ketone and Imidazolium‐Functionalized Polyphenylene Oxide for Vanadium Redox Flow Battery Applications. Issue 19 (7th October 2019) - Chu, Fuqiang; Chu, Xufeng; Lv, Teng; Chen, Zhouyi; Ren, Yurong; Zhang, Shuai; Yuan, Ningyi; Lin, Bencai; Ding, Jianning
Abstract: Amphoteric membranes were obtained from imidazolium‐functionalized polyphenylene oxide (ImPPO) and sulfonated poly(ether ether ketone) (SPEEK) for an all‐vanadium redox flow battery (VRFB) application. The SPEEK/ImPPO amphoteric membranes showed a considerably lower swelling degree and water uptake compared to those of pure SPEEK membranes, owing to the formation of ionic bonds between the cationic imidazolium groups of ImPPO and the anionic sulfonate groups of SPEEK. The cationic imidazolium groups of the ImPPO exhibited a Donnan exclusion effect on vanadium ions; therefore, the amphoteric membranes showed a much lower vanadium permeability than the pure SPEEK membrane. In addition, the vanadium permeability of the amphoteric membranes deceased with an increase in the ImPPO content. SPEEK‐ImPPO20 with 20 wt% ImPPO showed a vanadium permeability of 0.43×10 −9 cm 2 s −1 at room temperature, which is 17 times lower than that of Nafion 212 (8×10 −9 cm 2 s −1 ). The VRFB assembled with SPEEK‐ImPPO20 showed a coulombic efficiency of 97.2 % and a voltage efficiency of 85.8 % at a current density of 60 mA cm −2, whereas the values for Nafion 212 were 92.4 % and 86.7 % under the same conditions. In addition, the VRFB assembled with SPEEK‐ImPPO20 exhibited much better capacity retention than that assembled with Nafion 212. These results indicate that the SPEEK‐ImPPO amphoteric membrane is a promising material for VRFB applications. Abstract : SPEEK to me : Amphoteric membranes exhibit excellent properties that can be attributed to the formation of ionic bonds in the membranes. This study will open up new prospects for the preparation of ion exchange membranes with a high performance for the application of vanadium redox flow batteries.